Perbedaan Kemampuan Layup Putra Putri Sekolah Kelas Bawah - Wati, Isti Dwi Puspita (Indonesian Journal of Physical Education and Sport Science, 2023)
Studi purpose. This study aims to determine the ability of elementary school students, especially the lower classes, to do layups Materials and methods. The sample is 117 elementary school students, 52 boys, and 65 girls. The layup ability test is carried out by giving five opportunities to students. Admission is scored one, and non-entry is scored 0. Descriptive and non-parametric analysis is used to explain the data that has been collected. Results. The results showed little difference in the skill of laying up between boys and girls of low-grade elementary school students. This can be seen from the average layup ability and standard deviation values , which are not much different. This similarity is even more convincing when a non-parametric statistical test is carried out, which gives a significant count of 0.165 Conclusion. This concludes that there is no difference between boys and girls in the ability to do the lay up